A comparative study on students' beliefs concerning their autonomy in doing mathematics - Furinghetti, Fulvia; Pehkonen, Erkki (NOMAD Nordic Studies in Mathematics Education, 2000)
This paper treats an investigation on beliefs about autonomy held by 260 Finnish and 246 Italian seventh-grade students. The data were collected by means of a questionnaire consisting of 32 closed questions dealing with different aspects of mathematics teaching and learning, and three open questions on students' good and bad experiences in mathematics instruction and their wishes for good instruction. We have confined ourselves to the eight questions of the questionnaire identified as pertaining to the students' beliefs about autonomy in doing mathematics. The data was collected through the questionnaire allowed to outline the patterns of beliefs in each country and compare patterns with each other. We have identified a core of common patterns in the two countries which are mainly related to the issue of classroom interaction and to the students' need of their teacher's help. The biggest differences between the two countries were found in the items concerning the use of trial-and-error strategies and the possibility that the students solve mathematical problems on their own.